Radiation-Induced DNA Damage in Operators Performing Endovascular Aortic Repair. Issue 25 (19th December 2017) - El-Sayed, Tamer; Patel, Ashish S.; Cho, Jun S.; Kelly, James A.; Ludwinski, Francesca E.; Saha, Prakash; Lyons, Oliver T.; Smith, Alberto; Modarai, Bijan; Tyrrell, M; Gkoutzios, P; Abisi, S; et al.
Abstract : Background: Radiation exposure during fluoroscopically guided interventions such as endovascular aortic repair (EVAR) is a growing concern for operators. This study aimed to measure DNA damage/repair markers in operators perfoming EVAR. Methods: Expression of the DNA damage/repair marker, γ-H2AX and DNA damage response marker, phosphorylated ataxia telangiectasia mutated (pATM), were quantified in circulating lymphocytes in operators during the peri-operative period of endovascular (infrarenal, branched, and fenestrated) and open aortic repair using flow cytometry. These markers were separately measured in the same operators but this time wearing leg lead shielding in addition to upper body protection and compared with those operating with unprotected legs. Susceptibility to radiation damage was determined by irradiating operators' blood in vitro. Results: γ-H2AX and pATM levels increased significantly in operators immediately after branched endovascular aortic repair/fenestrated endovascular aortic repair ( P <0.0003 for both). Only pATM levels increased after infrarenal endovascular aortic repair ( P <0.04). Expression of both markers fell to baseline in operators after 24 hours ( P <0.003 for both). There was no change in γ-H2AX or pATM expression after open repair. Leg protection abrogated γ-H2AX and pATM response after branched endovascular aortic repair/fenestrated endovascular aortic repair. The expression of γ-H2AX varied significantly when operators' blood was exposed to the same radiation dose in vitro ( P <0.0001). Conclusions: This is the first study to detect an acute DNA damage response in operators performing fluoroscopically guided aortic procedures and highlights the protective effect of leg shielding. Defining the relationship between this response and cancer risk may better inform safe levels of chronic low-dose radiation exposure. Abstract : Supplemental Digital Content is available in the text.